Driving Factors Of Industry 4.0 Readiness Among Manufacturing Smes In Malaysia - Annie, Wong Pooi Hang (2022)
The fourth industrial revolution, also known as Industry 4.0, increases production efficiency and competitiveness of companies. However, implementation of Industry 4.0 is comparatively low in developing countries. Moreover, Malaysian manufacturing SMEs are still at their infancy stage of Industry 4.0 adoption. Hence, it signals the need to broaden the current state of knowledge in Industry 4.0 readiness of Malaysian manufacturing SMEs and the driving factors that play significant roles in strengthening SMEs' readiness for digital revolution in Malaysia. Based on the Resource Based View Theory, the present study builds a research framework to govern the investigation of organizational capabilities, SME institutional support, perceived advantage and market factors as the driving factors of Industry 4.0 readiness of Malaysian SME manufacturing firms, firm size as the moderating variable. Online questionnaire was sent to the owners and managers of Malaysian-owned manufacturing SMEs located throughout Peninsular Malaysia, which the firms have received some form of government assistance. A total of 110 owners or managers from Malaysian manufacturing SMEs participated in the research. The data collected were analysed using partial least squares structural equation modeling.